Critical review on the idea of dystopia - Babaee, Ruzbeh; Jujar Singh, Hardev Kaur; Zhang, Zhicheng; Zhang, Haiqing (Canadian Center of Science and Education, 2015)
The purpose of this review is firstly to show the formation of dystopia that finds its roots in utopia. Then, the foundation of dystopian fiction from the perspectives of such critics as Chad Walsh, Tom Moylan, Mark R. Hillegas, and Erika Gottlieb, among some others, is investigated. Finally, we briefly reveal the standing of Aldous Huxley, Kurt Vonnegut, and Don DeLillo, among many other dystopian writers, in depiction of dystopian societies. This study also attempts to explain how works of these three writers were revolutionary in their challenging of the new values that led to the degradation of human dignity.